Genotoxic and mutagenic effects of permethrin in mice: Micronuclei analysis in peripheral blood erythrocytes - Roma, Gislaine Cristina [UNESP]; de Oliveira, Patricia Rosa [UNESP]; Araujo, Andrea Mendez [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (Wiley-Blackwell, 2012)
Pyrethroids such as permethrin are synthetic compounds widely used in the agriculture of many countries to combat plagues and in domestic products, such as acaricides. Not so long ago these chemicals were characterized as non-toxic for non-target organisms; however, recent studies have showed that these compounds could present toxic potential for many organisms. In this sense, this study presents genotoxic and mutagenic potential of permethrin administered intraperitoneally in mice under artificial conditions by the use of micronucleus assay in the peripheral blood of these animals. The mice were divided into five groups: group I = negative control (distilled water), group II = positive control (cyclophosphamide), group III = 30% of permethrin LD50 (96 mg/kg), group IV = 50% of permethrin LD50 (160 mg/kg), and group V = 80% of permethrin LD50 (256 mg/kg). The peripheral blood was collected 24, 48, and 72 h after treatment. Results showed that all the tested permethrin dosages presented genotoxic and mutagenic effects 24 h after treatment, which would contradict the classification of this chemical product as moderately toxic, i.e., unable to cause damages to the cell DNA. Microsc. Res. Tech. (C) 2012 Wiley Periodicals, Inc.
Keywords: rodents; acaricides; Pyrethroids; DNA damage; micronucleus assay